Himalayan mobilities : an exploration of the impact of expanding rural road networks on social and ecological systems in the Nepalese Himalaya /: an exploration of the impact of expanding rural road networks on social and ecological systems in the Nepalese Himalaya. ([2017]) - Beazley, Robert E; Lassoie, J. P
No abstract available